Intercultural Coaching: Developing Educational Leadership in the United Arab Emirates - Cameron, Gregor Ewen (Curtin University, 2017)
This study backgrounds educational leadership reform in the United Arab Emirates. Various learning theory, coaching and mentoring approaches are considered within Stelter’s third-generation coaching model. Using the emerging, constant-comparative derivative of ‘grounded theory’, six case studies are analysed within an interpretive research paradigm. Data presentation and discussion considers the extent to which unique coaching and mentoring approaches are evident in this intercultural context and the set of factors that enhance or inhibit coaching relationships.